Digital Storytelling on Pandawara Group’s Digital Activism on TikTok - Pratiwi, Aprilianti; Farizal, Hanifah Fitri (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Digital Storytelling, which has been widely used for learning and marketing activities, is now also used by activists as a communication strategy for social change. One activist who utilizes digital storytelling for social change is Pandawara Group. They are five young men from Bandung, West Java who are very concerned about environmental cleanliness. Starting from cleaning up garbage scattered in the river near their home, now Pandawara Group has cleaned up a lot of garbage in the river and beaches outside the Bandung area. The aim of this study is to analyze digital storytelling on Pandawara Group’s digital activism on TikTok. This research is qualitative research using narrative analysis based on the narrative analysis framework developed by Connelly and Clandinin and Polkinghorne. The results of the research show that visual collaboration and narrative are used to persuade followers of the Pandawara Group TikTok account to participate in the garbage cleanup action on Teluk Beach. The results of the study found that in these three videos, Padawara Group through these three videos have presented a story with a clear and simple structure so that the plot is easy to follow. The background shown in all three videos shows a stark difference between the very dirty beach conditions in the first video, when it is cleaned in the second video, and after the beach is cleaned in the third video. The message conveyed by the three videos is also very efficient and focused on the main goal. It is necessary to include the stories of the characters involved to find out what their motivation is to participate in this beach clean-up action and the challenges they face in order to increase the emotional closeness of the audience to the story.